A QUALITATIVE INVESTIGATION How The Merdeka Curriculum Fosters Critical Thinking Among Students: A Qualitative Investigation - Situmorang, Arisdani; Selviana Napitupulu (CV Putra Publisher, 2026)
This mini-research investigates the impact of the Merdeka Curriculum on enhancing critical thinking skills among Indonesian students. Fostering critical thinking has become essential for both academic success and societal participation as educational contexts change. The Indonesian Ministry of Education launched the Merdeka Curriculum with the goal of establishing a flexible, student-centered learning environment that prioritizes creativity and critical thinking. The study examines the literature to determine important results and difficulties related to the implementation of this curriculum using a descriptive qualitative methodology that incorporates library research and systematic literature reviews. Results show that students' analytical abilities and engagement are greatly enhanced by project-based and experiential learning, which encourages deeper learning. The efficacy of the curriculum is hampered by issues including poor teacher preparation, a lack of resources, and pressure on students to choose their courses. This study emphasizes how important it is to resolve these implementation challenges in order to optimize the Merdeka Curriculum's advantages. The curriculum may greatly aid in the development of critical thinkers equipped to handle the complexity of the contemporary world by creating a supportive learning environment and empowering both instructors and students.